Cardiac sequelae after COVID-19: Results of a 1-year follow-up study with echocardiography and biomarkers - Matejova, Gabriela; Radvan, Martin; Bartecku, Elis; Kamenik, Martin; Koc, Lumir; Horinkova, Jana; Sykorova, Lubica; Stepanova, Radka; Kala, Petr (Frontiers in Cardiovascular Medicine, 2022)
Objective To evaluate the need for cardiac monitoring in unselected patients recovered from COVID-19 and to estimate the risk of heart complications after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Materials and methods During March 2020 and January 2021, 106 patients who had recovered from SARS-CoV-2 (alpha and beta variants) were enrolled in prospective observational cohort study CoSuBr (Covid Survivals in Brno). The diagnosis was based on a reverse transcription-polymerase chain reaction swab test of the upper respiratory tract. Demographic parameters, patient history, clinical evaluation, cardiac biomarkers, ECG and echocardiography were recorded during three visits (Visit 1 at least 6 weeks after infection, Visit 2 three months later, and Visit 3 one year after Visit 1). Results 58.5% of the study group (n = 106) were female, while the mean age was 46 years (range 18–77 years). The mean time interval between the onset of infection and the follow-up visit was 107 days. One quarter (24.5%) of the patients required hospitalization during the acute phase of the disease; the rest recovered at home. 74% suffered a mild form of the disease, with 4.8, 18.1, and 2.9% suffering moderate, severe, and critical forms, respectively. At the time of enrolment, 64.2% of the patients reported persistent symptoms, while more than half of the whole group (50.9%) mentioned at least one symptom of possible cardiac origin (breathing problems, palpitations, exercise intolerance, fatigue). In the 1-year follow-up after COVID-19 infection, left ventricle ejection fraction showed no significant decrease [median (IQR) change was −1.0 (−6.0; 4.0)%, p = 0.150], and there were no changes of troponin (mean change −0.1 ± 1.72 ng/L; p = 0.380) or NT-proBNP [median (IQR) change 2.0 (−20.0; 29.0) pg/mL; p = 0.315]. There was a mild decrease in right ventricle end diastolic diameter (-mean change 2.3 ± 5.61 mm, p < 0.001), while no right ventricle dysfunction was detected. There was very mild progress in left ventricle diastolic diameter [median (IQR) change 1.0 (−1.0; 4.0) mm; p = 0.001] between V1 and V3, mild enlargement of the left atrium (mean change 1.2 ± 4.17 mm; p = 0.021) and a non-significant trend to impairment of left ventricle diastolic dysfunction. There was a mild change in pulmonary artery systolic pressure [median (IQR) change 3.0 (−2.0; 8.0) mmHg; p = 0.038]. Conclusion Despite a lot of information regarding cardiac impairment due to SARS-CoV2, our study does not suggest an increased risk for developing clinically significant heart changes during the 1-year follow-up. Based on our results, routine echocardiography and biomarkers collection is currently not recommended after COVID-19 recovery.